Hairy Cell Leukemia: Report Of A Case With A Plasma Mediated Defect In Platelet Function And Platelet Morphology - Mattson, J C; Sanal, S (Thrombosis and Haemostasis, 1981)
A 60-year-old male with hairy cell leukemia developed purpura. Studies performed prior to splenectomy and at a time when purpuric lesions were present demonstrated a severe platelet functional defect characterized by absent primary and secondary wave aggregation with ADP and Ristocetin, absent Collagen aggregation, and diminished Epinephrine aggregation. In addition PF3 was decreased and the bleeding time prolonged. EM demonstrated a mixed population of degranulated, enlarged platelets and normal platelets. Following splenectomy PF3 levels and the bleeding time returned to normal. Repeat aggregation studied performed post-splenectomy showed return of primary wave aggregation but persistent absence of secondary wave aggregation in response to ADP, and virtually absent response to Collagen. Ristocetin aggregation returned to normal, but Epinephrine failed to produce any response. EM performed post-splenectomy demonstrated normal platelets. Tests performed on the patient’s pre-splenectomy plasma indicated the presence of an inhibitor which was capable of inhibiting primary aggregation, nucleotide release and secondary wave aggregation in normal platelets with all agents tested.This inhibitor had no effect on adhesion in a collagen adhesion assay. Full inhibitory effect was present after incubation of inhibitor plasma and normal platelets for 5 min. but with longer incubation times inhibition of aggregation was less pronounced suggesting either dissociation or destruction of the platelet bound inhibitor. Partial characterization of the inhibitor demonstrated that it was dialyzable, stable at 56 C for 30 min. and at 4 C for 72 hrs., and present in a 50% ammonium sulfate fraction of plasma. These studies suggest that the inhibitor is a globulin which appears to exert its inhibitory effect by nonspecific, easily dissociable binding to the platelet surface.